2022
DOI: 10.1038/s41428-022-00699-9
|View full text |Cite
|
Sign up to set email alerts
|

BIAN-based durable polymer metal complex as a cathode material for Li–O2 battery applications

Abstract: Among several strategies employed to reduce overpotential and achieve reliable reversibility with Li-O 2 batteries, the use of atomically dispersed bifunctional carbon catalysts is very attractive. However, most of the methods used to prepare these bifunctional oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts require high temperatures and exhibit low yields, and it is therefore difficult to predetermine the active sites qualitatively and quantitatively. Here, we propose the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The synthesis of the P-BIAN was performed using the procedure reported by Matsumi et al , The synthesis process of BIAN-LiPAA is shown in Figure . The synthesized polymer was successfully characterized via 1 H NMR and Fourier transform infrared (FT-IR) spectroscopy, and the results are shown in the Supporting Information.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the P-BIAN was performed using the procedure reported by Matsumi et al , The synthesis process of BIAN-LiPAA is shown in Figure . The synthesized polymer was successfully characterized via 1 H NMR and Fourier transform infrared (FT-IR) spectroscopy, and the results are shown in the Supporting Information.…”
Section: Synthesismentioning
confidence: 99%
“…Our previous studies have reported the robustness of BIAN-type conjugated polymer binders in graphite and Si-based anodes. , Structural highlights of the BIAN-type conjugated polymer binder are as follows: (a) the fused-planar naphthalene moiety of the polymer forms a π–π stacking interaction with the graphite skeleton, (b) the copper current collector clings to the diamine component of the polymer, allowing the binder to hold the electrode laminate intact on the current collector, and (c) the conjugated network of the polymer is provided by the BIAN-phenylene moiety as a component of the polymeric backbone, ensuring better electronic conductivity across the electrode matrix. , However, the Li + ion diffusion, R CT , and activation energy of lithiation of the anode can be further improved to enable XFC through additional binder design.…”
Section: Introductionmentioning
confidence: 99%
“…FAB180-Pt/Ir 1:1 sample was chosen for CV measurements in nonaqueous medium, prior to air-battery test. It is important to thoroughly assess the catalyst's performance in a non-aqueous electrolyte beforehand [15,28]. CV for FAB180-Pt/Ir 1:1 measured in nonaqueous medium is shown in figure 8.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…CV for FAB180-Pt/Ir 1:1 measured in nonaqueous medium is shown in figure 8. 0.1 M LiTFSI in TEGDME was used as nonaqueous electrolyte [28]. At the 50th cycle, the OER peak was not seen clearly around 1.41 V and ORR peak was seen in −1.75 V. After 100 cycles, change was seen around 1.21 V and −1.53 V. After 250 cycles the OER peak appeared more clearly.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation